Reintegration Prospects for the Ex-Convicts in Pakistan: A Legal Perspective - Aisha Tariq (Policy Perspectives, 2020)
The idea of smooth reintegration of ex-convicts back into the society after completion of their punishments has got statutory acknowledgement in many Western states. However, Pakistani legal regime seems divided regarding the readjustment prospects of these convicts. Each of several perplexing provisions incorporated in different statutes discusses an exclusive post-conviction circumstance by leaving the residual rehabilitation aspects untouched. Thus, these provisions lack a principle-based mechanism of exoneration of the ex-convicts. The absence of uniformity and consistency of rules not only deprives the majority of ex-offenders from the right to secure respectable reintegration into the society but the entire social order sometimes suffers due to grant of clemency to the wrong cases. The findings of this study suggest that a policy-based stance is required for the effortless readjustment of the ex-convicts in Pakistan who have desisted from crime. This policy perspective needs to be strengthened through an exclusive statute which also includes trivial details of the process to extend a principled chance of exoneration for such offenders.